Adaptive Motion of Animals and Machines
DOI: 10.1007/4-431-31381-8_8
|View full text |Cite
|
Sign up to set email alerts
|

On the Dynamics of Bounding and Extensions: Towards the Half-Bound and Gallop Gaits

Abstract: This paper examines how simple control laws stabilize complex running behaviors such as bounding. First, we discuss the unexpectedly different local and global forward speed versus touchdown angle relationships in the self stabilized SLIP. Then we show that, even for a more complex, energy conserving, unactuated quadrupedal model, many bounding motions exist, which can be locally open loop stable! The success of simple bounding controllers motivated the use of similar control laws for asymmetric gaits resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…The experiments with galloping robots demonstrate an emergent stability as a characteristic of gallop, which is thus constrained to the sagittal plane in transverse gallop. This research has also confirmed findings from simulations that rotary gallop has a tendency to generate circular trajectories (Poulakakis et al, 2006;Smith and Poulakakis, 2004). From these results, we argue that CPGs of cursorial mammals could potentially produce all the running gaits, from bound and half-bound to rotary gallop and transverse gallop.…”
Section: Quadruped Gallop Controlsupporting
confidence: 86%
“…The experiments with galloping robots demonstrate an emergent stability as a characteristic of gallop, which is thus constrained to the sagittal plane in transverse gallop. This research has also confirmed findings from simulations that rotary gallop has a tendency to generate circular trajectories (Poulakakis et al, 2006;Smith and Poulakakis, 2004). From these results, we argue that CPGs of cursorial mammals could potentially produce all the running gaits, from bound and half-bound to rotary gallop and transverse gallop.…”
Section: Quadruped Gallop Controlsupporting
confidence: 86%
“…Since the running speed can be stabilized using the constant touchdown angle, self-stabilization (Blickhan 1989;Full & Koditschek 1999;Cham et al 2004;Poulakakis et al 2005) at musculoskeleton is also involved in (ii). As the examples of the method (iii), we employed a 'response' as modulation of the CPG phase as described in §2e.…”
Section: Jindrichmentioning
confidence: 99%
“…Compared to the two-phase control scheme, which is widely employed in many hopping robots (e.g. [7], [8], [9], [10], [12]), the proposed open-loop control scheme introduces three major arguments which could be essential for our comprehensive understanding of legged locomotion. Firstly, the flow of information is unidirectional and there is no signal feedback loop running all through the legs and the body, but the loop is only local, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…During the stance phase, the robot controls for the problems (1) and (2), and during the flight phase, the problem (3) is dealt with. By following these design principles, it has been shown that monopod, biped, quadruped and hexapod robots were able to maintain the balance and control the forward velocity only by regulating the appropriate angle of attack at touchdown during a flight phase [9], [10], [11], [12], [13]. All these studies are based on a method in which there are two independent control phases, thus the robot needs to identify the flight/stance phase at every computational step by using contact detectors on the feet.…”
Section: Introductionmentioning
confidence: 99%